Comparison of volume guarantee and volume-controlled ventilation both using closed loop inspired oxygen in preterm infants: a randomised crossover study (CLIO-VG study) - Nair, Vrinda; Lal, Mithilesh Kumar; Gillone, Jenna; Kannan Loganathan, Prakash; Bachman, Thomas Edward (Archives of disease in childhood. Fetal and neonatal edition, 2022)
OBJECTIVE: The objective of this study was to compare two different modes of ventilation in maintaining oxygen saturation (SpO2) in target range (90%-95%) in ventilated preterm infants cared for with automatic control of oxygen delivery (A-FiO2). DESIGN: A single-centre randomised crossover study. SETTINGS: A level III neonatal intensive care unit. PATIENTS: Preterm infants receiving mechanical ventilation and oxygen requirement >21%. INTERVENTIONS: Volume guarantee (VG) vs volume controlled ventilation (VCV) modes with automatic oxygen control (A-FiO2). OUTCOMES: The primary outcome of this study was the proportion of time spent with oxygen saturations in the target range (90%-95%) . RESULTS: Nineteen preterm infants with a median gestation age 25 weeks (IQR: 24-28) and birth weight 685 g (IQR: 595-980) were enrolled in the study. There was no significant difference in primary outcome of median proportion of time spent in target saturation between the two arms (72% (57-81) in VG vs 75% (58-83) in VCV; p=0.98). There was no significant difference in the secondary outcomes of time spent in SpO2 <80% (0.03% vs 0.14%; p=0.51), time spent in SpO2 >98% (0.50% vs 0.08%; p=0.54), the median FiO2 (31% vs 29%; p=0.51) or manual adjustments carried out between VG and VCV, respectively. The number of episodes of prolonged hypoxaemia and hyperoxaemia were similar in the two groups. CONCLUSION: There was no significant difference in time spent in target SpO2 range between VG and VCV when A-FiO2 was used as the FiO2 controller in this crossover randomised control study. TRIAL REGISTRATION NUMBER: NCT03865069.
Keywords: klinické křížové studie; ventilace umělá s přerušovaným přetlakem; umělé dýchání; lidé; Infant, Premature; Humans; jednotky intenzivní péče o novorozence; kyslík; novorozenec; Cross-Over Studies; Oxygen; Respiration, Artificial; syndrom respirační tísně novorozenců; Intensive Care Units, Neonatal; neinvazivní ventilace; Respiratory Distress Syndrome, Newborn; Intermittent Positive-Pressure Ventilation; novorozenec nedonošený; Noninvasive Ventilation; oxymetrie; Oxygen Inhalation Therapy; oxygenoterapie; Oximetry; Infant, Newborn